Effects of Different Adduct Ions, Ionization Temperatures, and Solvents on the Ion Mobility of Glycans - Feng, Hao; Yamaguchi, Takumi (Molecules (Basel, Switzerland), 2025)
The structural analysis of glycans remains a major challenge due to their high isomeric complexity and conformational flexibility arising from diverse glycosidic linkages and dynamic three-dimensional structures. Ion mobility–mass spectrometry (IM–MS) has been attracting attention as a way to develop the structural analysis of glycans. In this study, the effects of ionization conditions—including different types of adduct ions, ionization temperatures, and solvent environments—on the ion mobility behavior of glycans were systematically investigated. IM–MS measurements of ethylamine-tagged glycans showed broad arrival time distributions of monoprotonated ions indicating the presence of multiple conformers of glycans. Increased ionization temperatures and the use of methanol as a solvent further broadened the distribution, suggesting the enhanced conformational dynamics of the glycan ions. In contrast, sodium adduct ions yielded narrower distributions, implying that the interactions between sodium ions and glycans constrained structural flexibility. These results demonstrate that ionization parameters have a significant impact on glycan conformational behavior and mobility in the gas phase. This study provides insights into the analytical conditions for IM–MS measurements of glycans and highlights the utility of this method as a powerful tool for elucidating glycan structure and dynamics.